Situation Report: Hungary, 8 September 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Gyorgy Lukacs Defended against Changes of Revisionism Need for Research on Hungarians Living Abroad Tourism: An Interim Balance Sheet News on Comecon Metallurgical Plant in USSR Problems of Power Supply Lajos Feher on Current Problems of the Co-operative Movement Repair of Flood Damage behind Schedule